Identification of Microplastic Abundance in Indonesia's Coastal Regions: A Review - Ramadhan Tosepu; Inda Rabbihim; Hikma Sri Nurwidiarni (Journal of Health Science and Pharmacy, 2025)
Background: The increasing use of plastic in daily life has contributed to the growing abundance of microplastics in Indonesia. Improperly managed plastic waste is frequently found in rivers, seas, and lakes. In aquatic environments, microplastics are persistent pollutants that can remain for extended periods. Their presence poses significant threats to environmental sustainability, disrupting ecosystem balance, threatening aquatic biota, and potentially impacting human health. Objective: This study aims to identify and describe the abundance of microplastics in Indonesia's coastal areas. Methods: This research employs a literature review approach, analyzing relevant articles and studies that report the occurrence and distribution of microplastics, particularly in the coastal regions of Indonesia. Results: Microplastics have been identified in various aquatic ecosystems across Indonesia, including in water columns, sediments, and the digestive tracts of fish. The types of microplastics commonly found include fibers, films, fragments, pellets, and foams. These microplastics primarily originate from the degradation of larger plastic materials that accumulate and pollute aquatic environments. Conclusion: Microplastic pollution represents a critical environmental challenge for Indonesia's aquatic ecosystems. The western part of Indonesia tends to exhibit a higher abundance of microplastics, primarily due to intensive human activities and higher population density. The presence of microplastics can adversely affect aquatic organisms, disrupt ecological balance, and pose potential health risks to humans through the food chain. Keywords: Coastal areas, Microplastics, Plastic pollution, Human activities, Ecosystems, Indonesia